PENGAMPUNAN DAN PERJANJIAN DALAM PEMIKIRAN HANNAH ARENDT - Jadi Lima (STT Reformed Injili Internasional, 2014)
According to Hannah Arendt, human capacity to forgive and to make and keep a promise, can be a better solution for the inherent predicament of action than the more popular paradigm of control. Platonic cure for the triple predicament of action is to substitute ‘making for acting’. This dangerous substitution can be traced in the use of metaphors originated in the process of fabrication in the political arena. This leads to alienation, oppression, domination, violence in the course of Western history. The pluralities and equalities of voices indeed lead to uncertainty of the future, hence a lost sense of control, but Arendt believes the power inherent in the human capacity to make promises and to forgive as a better option than substituting ‘making for acting’. This article will retrace the Judeo-Christian roots of Arendt’s thought, evaluate her use of the sources, and appropriate her insights to get a better understanding of the political situation in Indonesia.